The use of scaffolding strategies among ESL learners in the comprehension of literary texts - Rafik - Galea , Shameem; Nair, Premalatha (Atma Jaya Catholic University, 2008)
Research involving comprehension among adult learners has been tremendously influential in the field of learning. This has led researchers across various disciplines to study the strategies adult learners use in an attempt to gain understanding of materials read. For example studies conducted by O’Malley and Chamot (1985)involving beginning and intermediate ESL students resulted in identification of 26 language learning strategies. On the other hand, Kalmbach (1986) identifies retelling as a form of strategy that could enhance comprehension among learners. One interesting aspect highlighted by the sociocultural theory is the use of scaffolding as a form of strategy to make sense of information. Various researches carried out in this field have shown the importance and effectiveness of scaffolding strategy. For example, studies by Donato & McCormick (1994) and Anton & DiCamilla (1998) on second language users of English have identified several scaffolding strategies that assist learners in gaining knowledge. Bearing this view in mind, this paper discusses how a group of teacher trainees of differing proficiency levels attempt to create meaning of two selected short stories. The study mainly focuses on the types of scaffolding utilized by teacher trainees from three different levels of proficiency; dyads of high proficiency, dyads of low proficiency and dyads of mixed proficiency. Based on the transcripts of the recorded discussions, the findings indicate that the types of scaffolding utilized by the respondents differ based on their proficiency levels.